2013
DOI: 10.5414/cp201836
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4/5 polymorphisms affect the blood level of cyclosporine and tacrolimus in Chinese renal transplant recipients

Abstract: Genetic polymorphisms of CYP3A5*3 and CYP3A4*18B may be partly responsible in large interindividual variability of cyclosporine and tacrolimus blood levels in Chinese renal transplant patients during the first month after transplantation. A patient carried combined genotype of CYP3A4*1/*1-CYP3A5* 3/*3 might require lower tacrolimus doses to achieve target concentration levels. Genotyping of CYP3A4*18B and CYP3A5*3 before transplantation is of benefit in determining a suitable initial dose for each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Few studies have examined the relationship between the CYP3A5 polymorphism and tacrolimus level in liver transplant patients. Moreover, the findings from these studies are inconsistent: some results showed that the receptor genotype has important implications for the metabolism of tacrolimus (Li et al, 2013;Spierings et al, 2013;Zhang et al, 2013), while other studies showed that blood tacrolimus level is more closely associated with the donor genotype (Barry and Levine, 2010;De Jonge et al, 2012;Valente et al, 2013).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Few studies have examined the relationship between the CYP3A5 polymorphism and tacrolimus level in liver transplant patients. Moreover, the findings from these studies are inconsistent: some results showed that the receptor genotype has important implications for the metabolism of tacrolimus (Li et al, 2013;Spierings et al, 2013;Zhang et al, 2013), while other studies showed that blood tacrolimus level is more closely associated with the donor genotype (Barry and Levine, 2010;De Jonge et al, 2012;Valente et al, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…Some previous studies in renal, lung, and heart transplantation have confirmed the contribution of the CYP3A5 polymorphism to individual differences in the response to tacrolimus (Hesselink et al, 2003;Zheng et al, 2003Zheng et al, , 2004Macphee et al, 2005;De Jonge et al, 2012;Li et al, 2013;Spierings et al, 2013;Zhang et al, 2013). However, in liver transplantation, the contribution of donor liver and recipient gut on tacrolimus metabolism increases the complexity of the mechanism of tacrolimus metabolism.…”
Section: Influence Of Age Time Course and Graft Liver Weight On Thementioning
confidence: 99%
“…Numerous studies on tacrolimus pharmacokinetics in transplant recipients consistently reported that carriers of CYP3A5*3/*3 genotype require significantly lower doses for both induction and the maintenance phase of the therapy (2838). Similar effects of CYP3A5 polymorphism on cyclosporine levels have been detected, but the reports remained largely inconsistent (29, 37, 3941). …”
Section: The Impact Of Genetic Polymorphisms On the Metabolism And Trmentioning
confidence: 74%
“…In renal transplant patients, significantly lower daily tacrolimus dose requirements were observed in carriers of CYP3A4*18 and *22 alleles (41, 4547), especially in CYP3A5 non-expressors (4850). The same, but usually less, pronounced effect was detected in transplant recipients on cyclosporine therapy (40, 47, 48).…”
Section: The Impact Of Genetic Polymorphisms On the Metabolism And Trmentioning
confidence: 99%
“…This results suggested that the metabolic activity of the CYP3A4*18 was relative stabilized at the early stage after LDLT when compared with the CYP3A5*3 and MDRR1-3435, and corresponded that the CYP3A4*18B genotype affects cyclosporine A pharmacokinetics during the first month following surgery in Chinese renal transplant recipients. Patients with CYP3A4*18B alleles may require higher doses of cyclosporine A to reach the target levels [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%